Given that , and are positive integers find the a solution that minimizes while satisfying the Diophantine equation
Enter your answer as .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This can be solved through casework. n is a positive integer, so we check the first few possibilities for n 2 .
Case 1: n = 1
Then a 2 b − a b 2 = 1 . Then a b ( a − b ) = 1 . This implies that both a b and a − b are equal to 1 (they cannot both be − 1 as a and b are positive, and so a b is too). In fact, for any n , a b and a − b will have to be factors of n 2 . Now, a b = 1 implies that a = b = 1 , but then a − b = 0 , and not 1 as needed. So the case n = 1 has no solutions.
Case 2: n = 2
Then a b ( a − b ) = 4 . This implies that pair of numbers ( a b , a − b ) is equal to either the pair ( 1 , 4 ) or the pair ( 2 , 2 ) . We can analyze these two subcases separately. Again, as before, a b is not equal to 1 , so say it is equal to 4 . Then the pair ( a , b ) is either the pair ( 1 , 4 ) or the pair ( 2 , 2 ) . Neither of these cases satisfy a − b = 1 . So the pair ( a b , a − b ) is not the pair ( 1 , 4 ) . If it is the pair ( 2 , 2 ) , then a b = 2 . Then the pair ( a , b ) is the pair ( 1 , 2 ) . This doesn't satisfy a − b = 2 . So the case n = 2 has no solutions.
Case 3: n = 3
This case has similar analysis to case 2. Here, a b ( a − b ) = 9 . As in case 2, this implies that the pair of numbers ( a b , a − b ) is equal to either the pair ( 1 , 9 ) or the pair ( 3 , 3 ) . a b is not equal to 1 , so say it is equal to 9 . Then the pair ( a , b is the pair ( 3 , 3 ) , which does not satisfy a − b = 1 . So ( a b , a − b ) is not ( 1 , 9 ) . Then it is the pair ( 3 , 3 ) . Then a b = 3 . Then the pair ( a , b ) is the pair ( 1 , 3 ) , which does not satisfy a − b = 3 . So the case n = 3 has no solutions.
Case 4: n = 4
Here, a b ( a − b ) = 1 6 . In this case, there are a few more options for the factors of 16. Doing analysis similar to that in cases 2 and 3, we find that the only solution here is a = 4 , b = 2 . So we have a solution of a = 4 , b = 2 , n = 4 . All that is left to do is to prove that this combination minimizes the sum a + b + n .
The solution of a = 4 , b = 2 , n = 4 gives a sum of a + b + n = 1 0 . Now, let n = 5 + x , where x is a non-negative integer. We get to say this, as we have already considered cases where n < 5 . So now, with n = 5 + x , we now try to find a solution a , b , n where the sum is less than 1 0 . This sum will be a + b + ( 5 + x ) < 1 0 , or a + b + x < 5 . Therefore, the sum a + b can be at most 4 . From this, using the fact that a > b , we get that the only possible remaining option is a = 3 , b = 1 . This means that a 2 b − a b 2 = 6 . But with n > 4 , n 2 > 1 6 , and therefore, 6 < n 2 . Therefore, for n > 4 , there is no solution a , b , n where a + b + n is less than 1 0 . Therefore the solution of a = 4 , b = 2 , n = 4 gives this minimal sum. Then we simply give the answer as ( a + b + n ) 2 = 1 0 0 .
So our final solution is a = 4 , b = 2 , n = 4 with a + b + n = 1 0 , and ( a + b + n ) 2 = 1 0 0 .